2005
DOI: 10.1063/1.2038187
|View full text |Cite
|
Sign up to set email alerts
|

Compression test system for a single submicrometer particle

Abstract: Articles you may be interested inA novel integrated tension-compression design for a mini split Hopkinson bar apparatus Rev. Sci. Instrum. 85, 035114 (2014); 10.1063/1.4868593 A method for intermediate strain rate compression testing and study of compressive failure mechanism of Mg-Al-Zn alloy A compression test system was developed for measuring the strength of a single particle with a cross-sectional dimension of less than 1 m. The test system used a small diamond plate that has a flat platen to compress the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 9 publications
3
22
0
1
Order By: Relevance
“…[38] This value was close to the value obtained for maximum impact pressure in the simulation meaning that the a-Al 2 o 3 starting particle is most likely to be fractured during impaction. From these results, it was concluded that the dense structure occurs due to the reduction of crystallite size by fracture or plastic deformation at room temperature during the AD process.…”
Section: Densification Mechanism Of Ceramic Layers In Ad Processsupporting
confidence: 77%
“…[38] This value was close to the value obtained for maximum impact pressure in the simulation meaning that the a-Al 2 o 3 starting particle is most likely to be fractured during impaction. From these results, it was concluded that the dense structure occurs due to the reduction of crystallite size by fracture or plastic deformation at room temperature during the AD process.…”
Section: Densification Mechanism Of Ceramic Layers In Ad Processsupporting
confidence: 77%
“…As we shall see, these particles are large enough to be in the inverse square root scaling regime which, according to equations (3) and (4), is independent of the compressive yield stress Y . Yoshida et al [2005] have extended this data set to submicron particle sizes by using a modified hardness testing apparatus to measure the strength of Al 2 O 3 particles with diameters near 0.7 μ m. For these experiments the reported loading rate corresponds to a strain rate of ≈ 10 −4 s −1 . In Figure 5, which is an expanded portion of Figure 2, this strain rate at 300 K yields a flow stress of σ s / μ = 0.031, which corresponds to a compressive yield stress of Y / μ = 2 σ s / μ = 0.062.…”
Section: Measured Compressive Strength Of Al2o3 Microspheresmentioning
confidence: 99%
“…Contrary to fibre-reinforced material, the role of the matrix cannot be limited to transferring the load across reinforcing elements: the local redistribution of stress around a broken particle involves the matrix much more extensively than with aligned, parallel fibres. Another important difficulty (or, at present at least, limitation) is that, unlike continuous fibres, the strength of particulate reinforcement has so far not been directly measured-although a first pioneering effort can be found in Yoshida et al (2005).…”
Section: Nomenclaturementioning
confidence: 98%
“…This is clearly approximate, if only because little is known of the fracture of small, brittle particles such as those typically found in metallic alloys or composites. Data for particle strength are, with only few exceptions (Yoshida et al, 2005), nearly always indirect measures based on composite data analysed making a priori the assumption that Weibull statistics are obeyed (Bré chet et al, 1991;Lahaie et al, 2004;Lewis, Withers, 1995;Llorca et al, 1993). How to measure particle strength remains a largely open question; progress on this question would be most interesting because it has strong implications concerning the design and engineering potential of ceramic particle-reinforced materials.…”
Section: Model Limitationsmentioning
confidence: 98%